Serum neopterin as well as ferritin, soluble interleukin-2 receptor, KL-6 and anti-MDA5 antibody titer provide markers of the response to therapy in patients with interstitial lung disease complicating anti-MDA5 antibody-positive dermatomyositis. Issue 5 (3rd September 2019) - Nishioka, Aki; Tsunoda, Shinichiro; Abe, Takeo; Yoshikawa, Takahiro; Takata, Miki; Kitano, Masayasu; Matsui, Kiyoshi; Nakashima, Ran; Hosono, Yuji; Ohmura, Koichiro; Mimori, Tsuneyo; Sano, Hajime
Abstract: Objective : This study identified biomarkers that can be used to assess disease activity and response to therapy in patients with interstitial lung disease complicating anti-melanoma differentiation-associated gene 5 (MDA5) antibody (Ab)-positive clinically amyopathic dermatomyositis (CADM). Methods : In 15 patients with interstitial lung disease complicating anti-MDA5 Ab-positive CADM, anti-MDA5 Ab, neopterin, interleukin (IL)-18, ferritin, and soluble interleukin 2 receptor (sIL-2R) levels were measured in cryopreserved serum specimens before and at multiple times after remission induction therapy, and their correlations were assessed. Results : Anti-MDA5 Ab, neopterin, IL-18, ferritin, and sIL-2R levels did not differ significantly between patients who survived and those who succumbed to the disease. In many cases, serum anti-MDA5 Ab titers were over the upper limit (over 150 index value) before treatment in the usual measuring method, and gradually decreased to the normal range at stable phase. Meanwhile, serum neopterin levels (21.6 [15.3–48.3] nmol/L) were significantly elevated in newly diagnosed patients and fell to 6.8 (5–11.4) nmol/L at 6 months after treatment introduction. Conclusions : Elevated serum neopterin as well as ferritin, sIL-2R, KL-6, and anti-MDA5 Ab titer might help identify patients with interstitial lung disease complicated with DM and might be useful in monitoring response to therapy.